Social exclusion and culture: The role of group norms, group identity and fairness - Hitti, Aline; Lynn Mulvey, Kelly; Killen, Melanie (Anales de Psicología / Annals of Psychology, 2011)
This paper reviews the literature on social exclusion in childhood and adolescence, with a focus on exclusion based on culture in which norms, identity, and fairness are salient factors. Recent research has examined children’s views about the fairness of exclusion in different social contexts, identifying the factors that contribute to legitimizing or rejecting the exclusion of members of out-groups. Across cultures, factors of relevance include gender, race, ethnicity, and culture. We review current findings and point to areas for new research.